Analysis of Health Problems as A Service Planning For the Control of Tuberculosis Disease in Magetan District, East Java - Yulastari W; Martini S; Purnomo Y (Malahayati Nursing Journal, 2024)
ABSTRACT This research is a study to determine what health problems or diseases need to be prioritized in health programs. The aim of the study was to determine the priority of public health problems in Magetan District. This study was an observational descriptive study conducted during January-February 2022. Prioritization of problems using the Basic Priority Rating System and PEARL methods then identifying the causes of problems using path analysis diagrams.  The determining the priority of the problem obtained that tuberculosis is the top priority. Identification of tuberculosis problems through path analysis diagrams showed that early detection activities in special places were low, screening of at-risk groups was not optimal, recording and reporting in hospitals and independent practitioners were low and suspects did not submit sputum back were the causes of low tuberculosis discovery. The results of the pathway analysis diagram are used as prevention planning such as optimizing health human resources, increasing community participation, multisectoral in TB elimination, improving the quality and quantity as well as equitable distribution of health resources, optimizing officers related to SITB reporting, forming coordination teams in each RT in contact investigation, increasing community knowledge with health promotion activities through counseling integrated with other programs. Keywords: Health Analysis, Tuberculosis, Magetan District